Adjuvant Anthracyclines in Breast Cancer: What Is Their Role?. (17th August 2018) - Shah, Ami N.; Gradishar, William J.
Abstract: : Anthracyclines have been a mainstay of breast cancer therapy for decades, with strong evidence demonstrating their impact on breast cancer survival. However, concerns regarding rare but serious long‐term toxicities including cardiotoxicity and hematologic malignancies have driven interest in alternative adjuvant therapy options with more favorable toxicity profiles. This article provides an update of data that help inform clinicians of the role anthracyclines should play in adjuvant breast cancer therapy. Two recently reported large randomized trials—the Anthracycline in Early Breast Cancer and Western German Study Plan B studies—compared a taxane and cyclophosphamide regimen with an anthracycline, taxane, and cyclophosphamide regimen. Although the studies had conflicting results, together these studies suggest that the benefit of adjuvant anthracycline therapy over a nonanthracycline taxane‐containing regimen is modest at best and may be primarily seen in patients with especially high‐risk disease (i.e., triple‐negative breast cancer, involvement of multiple lymph nodes). A third study—the MINDACT study—compared an anthracycline‐based regimen to a nonanthracycline regimen, with similar outcomes in both groups. Despite the toxicities, no adjuvant breast cancer regimen has been shown to be superior to an anthracycline‐taxane regimen in high‐risk patients. These data can directly inform clinical decision‐making in determining which patients warrant use of adjuvant anthracycline therapy. Future research may focus on confirming subgroups for whom it is reasonable to forgo adjuvant anthracyclines and validating predictive biomarkers or scores for anthracycline benefit. Implications for Practice: In patients with early breast cancer, the choice of adjuvant chemotherapy should be based on its effectiveness in reducing breast cancer recurrences and its short‐ and long‐term toxicities. Although adjuvant anthracycline and taxane chemotherapy has the most data supporting its effectiveness, anthracyclines carry a small but important increased risk for cardiotoxicity and leukemia. Two recent clinical trials help describe the degree of benefit with adjuvant anthracycline therapy compared with taxane therapy alone. They suggest that in patients with hormone receptor‐positive breast cancer and limited lymph node involvement, nonanthracycline taxane‐based adjuvant therapy may be adequate. Abstract : This article provides context for the value and risks of adjuvant anthracyclines, focusing on recently reported evidence of disease and patient characteristics that influences decision making regarding the use of adjuvant anthracyclines.